Effectiveness of Android-Based Learning Media “7 Minutes Workout” on the Motivation and Activity of Junior High School Students - Tomy Angga Pratama; Waris; Rina Sugiarti Dwi Gita (Postgraduate, University of Mataram, 2025)
This study examines how the